The fallacies of network neutrality regulation - Günter Knieps; Patrick Zenhäusern (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2007)
In this paper, historical functionalities of the traditional Internet are contrasted with today's Internet functionalities of the smart Internet architecture. It is shown that network neutrality regulation prohibiting congestion management and traffic quality differentiation is contrary to economically founded allocation mechanisms. By access regulation of local loop bottleneck components the transfer of market power from the telecommunications infrastructure into the complementary Internet access service markets can be avoided. Regulation between access service providers and Internet application service providers is not only superfluous but detrimental.
Keywords: 330; Internet; Netzzugang; Vertikale Konzentration; Wettbewerbsbeschränkung; Wettbewerbspolitik